2015
DOI: 10.1007/s00261-015-0611-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk of contrast-induced nephropathy for patients receiving intravenous vs. intra-arterial iodixanol administration

Abstract: Elevation in serum creatinine due to intravenous and intra-arterial iodixanol administration is infrequent and is not more common than after unenhanced CT scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
1
16
1
1
Order By: Relevance
“…In our study, the rates of CIN after IA contrast were numerically greater than IV contrast (16.5 vs. 12%), but this was not statistically significant, which is consistent with previous literature [11,14]. However, results from older clinical trials comparing different contrast media suggest that IV contrast carries a lower risk of CIN than IA contrast administration [12,15].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our study, the rates of CIN after IA contrast were numerically greater than IV contrast (16.5 vs. 12%), but this was not statistically significant, which is consistent with previous literature [11,14]. However, results from older clinical trials comparing different contrast media suggest that IV contrast carries a lower risk of CIN than IA contrast administration [12,15].…”
Section: Discussionsupporting
confidence: 80%
“…The rate of CIN AKI in patients who received IA contrast (16.5%) is similar to the rates described in CKD populations [9]. On the other hand, the rate of CIN AKI after IV contrast (12.5%) was higher than previously reported rates of 2-4% [11,12] in the general population and closer to those reported in CKD populations, ranging from 2.5 to 11% [2,7,13]. This slightly higher incidence can be explained by the higher risk population analyzed in this study (inpatient CKD) along with the more conservative definition of AKI used for our analysis (0.3 mg/dL rather than 0.5 mg/dL).…”
Section: Discussioncontrasting
confidence: 39%
“…As background, there were a number of cases that satisfied the diagnostic criteria for CIN due to natural fluctuations of SCr, including patients who did not receive contrast media [145]. After the publication of the CIN guideline 2012, a number of large-scale researches have been published that retrospectively analyzed the risk factors for CIN by applying strict statistical methods and using non-contrast media groups as controls, and they showed that the risk of developing CIN with intravenous administration of contrast media was lower than previously thought [24,102,[146][147][148][149][150][151][152][153][154][155][156][157][158].…”
Section: Level Of Evidence: Iva/grade Of Recommendation: B (Minds 201mentioning
confidence: 99%
“…Therefore, when a patient in an intensive care unit develops AKI after contrast-enhanced CT, it is very difficult to determine whether it has been caused by contrast media or not. In recent years, several reports have been conducted to verify the risk of developing CIN in intensive care and emergency outpatient patients [102,152,154,156,[164][165][166][167][168][169][170].…”
Section: Rationale Cq6-2mentioning
confidence: 99%
“…Furthermore, PC-AKI may be associated with increased risk for hemodialysis, mortality, longer hospital admissions and greater healthcare costs (46). However, other studies have questioned these implications by asserting a lack of causal evidence between contrast and renal injury as well as an overestimation of PC-AKI in the presence of physiologic creatinine fluctuations (710). …”
Section: Introductionmentioning
confidence: 99%